Valuing wind farms’ environmental impacts by geographical distance: a contingent valuation study in Portugal - Botelho, Anabela (2013)
Wind energy is currently one the most important energy sources in the production of electricity. In this study, we use the CVM to elicit the monetary value attached to wind power’s environmental impacts from three different groups of individuals: local residents, residents in a nearby town, and residents outside the area of a wind farm located in Portugal, one of the top 10 countries in the world with the highest cumulative wind power capacity to date. In each case, our empirical analysis employs a novel likelihood function that is constructed to be appropriate for the type of data collected. The main results are supportive of a NYMBY effect, but also indicate that the amount needed to compensate local residents for the negative impacts caused by the wind farm can be raised by the constitution of a compensation fund paid by non-residents, thereby overcoming the inefficiency caused by the NYMBY effect.